Effectiveness of the rhabdomyolysis treatment protocol in critically ill trauma patients at the level I trauma center - Promrat, Pariwat; Chotirosniramit, Narain; Chandacham, Kamtone; Jirapongjareonlap, Tidarat; Chittawatanarat, Kaweesak (Biomedical Sciences and Clinical Medicine, 2017)
Objective Rhabdomyolysis and its consequence, acute renal failure, is a serious complication with high mortality rate. However, its treatment differs among individual physicians. Therefore, the rhabdomyolysis treatment protocol was established by the multidisciplinary experts’ consensus in July 2008. The objective of this study was to evaluate the effectiveness of the rhabdomyolysis treatment protocol after implementation in critically ill trauma patients. Material and methods A retrospective chart review on rhabdomyolysis patients was performed between 1st January 2006 and 31thDecember 2010, and de fi ned as total creatine phosphokinase (CK) of more than 3,000 U/L. The patients admitted before and after July 2008 were de fi ned as the pre- and post- protocol group, respectively. The demographic data, disease severity, fl uid administration, and outcomes were recorded. Statistical signi fi cance was de fi ned as p<0.05. Results A total of 659 patients was admitted into this study, with investigation of CK being made during the study period. Of these patients, 267 had rhabdomyolysis (29 and 238 in the pre- and post-protocol group, respectively). There was a statistically signi fi cant difference in the occurrence of acute kidney injury (pre-protocol group vs. post-protocol group: 51.7% vs. 29.4%; p=0.015), and acute dialysis requirement (13.8% vs. 3.6%, p=0.01). The mortality rate of patients requiring long term dialysis, and the creatinine level at discharge were no different between the two groups. Mixed model analysis of the clinical and laboratory parameter, during 14 days of admission, showed a signi fi cant decrease of CK (p<0.001), decrease of creatinine (p<0.001), higher urine pH monitoring (p=0.005), less mannitol administration (p<0.001), and higher administration of sodium bicarbonate (p=0.006) in the post-protocol group Conclusion The rhabdomyolysis treatment protocol is effective in terms of acute renal failure, acute dialysis, and decreasing CK and serum creatinine level in rhabdomyolysis post-trauma patients. Limitation This was a retrospective study. The data recorded in the pre-protocol period were incomplete, and the CK was not investigated routinely during this time.